FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI DI KECAMATAN BATURAJA BARAT DAN KECAMATAN LENGKITI KABUPATEN OGAN KOMERING ULU - Dika Apriani (Universitas Bina Taruna Gorontalo, 2024)
This research aims to analyze the factors that influence employee performance in West Baturaja District and Lengkiti District, Ogan Komering Ulu Regency. This research uses a quantitative approach. Data was collected through a survey method by distributing questionnaire instruments to 36 employees of West Baturaja District and Lengkiti District, Ogan Komering Ulu Regency as the research population. The analytical method used is tabulation to answer the research objectives of Likert tables and regression analysis is used. The variables in this research are, the independent variables are Leadership, Work Environment and Work Motivation. The dependent variable is employee performance. The results of the research analysis show that Leadership has a positive and significant influence on Employee Performance, the Work Environment also has a positive and significant influence on Employee Performance, Work Motivation also has a positive and significant influence on Employee Performance. Thus, agencies are advised to pay more attention to leadership, work environment and work motivation on performance because they can influence performance directly or indirectly.